Diagnostic and phylogenetic character variation in the genus Canthon Hoffmannsegg and related genera (Coleoptera: Scarabaeidae: Scarabaeinae) - Scholtz, Clarke H. (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2007.